Pengaruh Dewan Komisaris Dan Komite Audit Terhadap Kinerja Keuangan Perbankan Syariah Yang Terdaftar Di Bank Indonesia - Mulianita, Asti; Sutarti, Sutarti; Triandi, Triandi (Jurnal Ilmiah Akuntansi Kesatuan, 2019)
The research is aimed at studying (1) the impact of Board of Commissioners on the financial performance of sharia banking listed in Bank Indonesia for 2011-2014 periods, (2) the impact of Audit Committees on the financial performance of sharia banking listed in Bank Indonesia for 2011-2014 periods, and (3) the impact of Board of Commissioners and Audit Committees on the financial performance of sharia banking listed in Bank Indonesia for 2011-2014 periods. The population is all sharia banks listed in Bank Indonesia during the 2011-2014 periods amounted of 11 banks. Samples were selected through purposive sampling. The analysis techniques used are classical assumption and double linear regression test. The results show that Board of Commissioners has significantly negative impact on the financial performance of sharia banking. Meanwhile, the Audit Committees has no impact on the same subject. Both Board of Commissioners and Audit Committees impacted the financial performance of sharia bank significantly.